Risk assessment and hierarchical classification of foodborne disease epidemics during major events in Beijing: an empirical study based on surveillance data analysis - Jinru JIANG; Yangbo WU; Tongyu WANG; Chao WANG; Yanlin NIU; Di WANG; Liping LI; Qian CHEN; Yao ZHAO; Xiaochen MA (Zhongguo gonggong weisheng)
ObjectiveTo develop a theoretical grading method for foodborne disease risk assessment during major events in Beijing, using a major sports event as an example, and to provide references and experiences for foodborne disease risk assessment during other major events in China. MethodsAccording to the World Health Organization's list of foodborne diseases, combined with the foodborne diseases monitored by the Beijing Foodborne Disease Surveillance System during the major sports event from 2016 to 2020 (November to April of the following year) as risk factors, the risk levels of foodborne diseases in the key population and the general population of a major sports event in Beijing were evaluated using the risk matrix method and the Borda count method. ResultsA total of 25 foodborne disease risk factors were identified in 3 major categories and 7 subcategories. The risk levels of foodborne disease in both the key population and the general population were concentrated in the high risk (H), moderate risk (M), and low risk (L) levels. For the key population, there were 5 H-level risk factors (20%), 11 M-level risk factors (44%), and 9 L-level risk factors (36%), of which rodenticides and tetrodotoxin poisoning were the most important risk factors. For the general population, there were 4 H-level risk factors (16%), 6 M-level risk factors (24%), and 15 L-level risk factors (60%). Among them, norovirus and kidney bean poisoning were the most important risk factors. ConclusionsFoodborne disease risk assessment for major events should be based on the characteristics of the event, previous experience with major events, and foodborne disease surveillance data from the same period. Prevention measures should focus on high and medium risk factors and those at the top of the Borda ordinal, and carry out monitoring and testing in the procurement, storage, processing and other links of raw materials, formulate recipes scientifically, do a good job in personnel health and training, and prevent cross-contamination.